Multiply and Then Verify : −3x2y2 And (X – 2y) for X = 1 and Y = 2. - Mathematics

Advertisement Remove all ads
Sum

Multiply and then verify :
−3x2y2 and (x – 2y) for x = 1 and y = 2.

Advertisement Remove all ads

Solution

(−3x2y2) × (x – 2y)

= (−3x2y2) × (x) − (−3x2y2)(2y)

= −3x2y2 + 6x2y3

= 6x2y3 − 3x3y2

For x = 1 and y = 2

(−3x2y2) × (x – 2y)

= (−3 × 12 × 22) × (1 − 2 × 2)

= (6 × 1 × 8) − (3 × 1 × 4)

= 48 − 12

= 36 

∴ For x = 1 and y = 2, it is verified that,

(−3x2y2) × (x – 2y)

= 6x2y3 − 3x3y2

Concept: Multiplying a Polynomial by a Polynomial
  Is there an error in this question or solution?

APPEARS IN

Selina Concise Mathematics Class 8 ICSE
Chapter 11 Algebraic Expressions
Exercise 11 (C) | Q 13 | Page 143
Advertisement Remove all ads
Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×